MINI RIVIEW: POTENSI ASAM MALAT (2-hydrobutanedioic-acid) DAN TURUNANNYA SEBAGAI SURFAKTAN - Rachmat, A. Khafifah Dwi; Daniel, Daniel; Pasaribu, Subur P. (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Malic acid (2-hydrobutanedioic-acid) is a dicarboxylic acid (carboxylic acid) which is generally found in many apples. Several malic acid derivatives have been synthesized through esterification and amidation reactions, including methyl malate, maleyl oleate and maleyl glutamide. Based on the results of FT-IR analysis of malic acid, it is known that there is an absorption peak at wave number 3448.72 cm¬-1 indicating the presence of an alcohol group and an absorption peak at wave number 1720.50 cm-1 indicating the presence of a carboxylic group. In methyl malate, it is known that in the wave number area of ​​1735.93 cm-1, stretching vibrations of the C=O ester carbonyl group occur. In maleyl oleate, the absorption in the wave area of ​​1743.65 cm-1 is a typical absorption from the stretching vibration of C=O ester. In maleyl glutamide, it is known that there is absorption at the peak wave number of 3425.58 cm-1 which is the stretching vibration of the NH (amide) group. The results of several literatures explain that the malic acid derivative, namely methyl malate, has an HLB value of 11.2 and can be used as an O/W (Oil in Water) emulsifier. The HLB value of maleyl oleate has a value of 4.61 which can be used as a W/O (Water in Oil) emulsifier and for maleyl glutamide the HLB is 14.84 which can be used as an O/W (Oil in Water) emulsifier. Therefore, malic acid derivatives have potential as materials for surfactant synthesis. Keywords: Malic Acid, Esterification and HLB (Hydrophilic Lipophilic Balance).